2011
DOI: 10.1179/107902611x12971826988174
|View full text |Cite
|
Sign up to set email alerts
|

Speech-language pathology treatment time during inpatient spinal cord injury rehabilitation: the SCIRehab project

Abstract: The need for swallowing and cognitive treatment by SLP is common during inpatient rehabilitation due to dysfunction resulting from use of artificial airways and feeding approaches, as well as secondary brain injuries. The large amount of variability seen in SLP treatment time, which is not explained well by patient and injury characteristics, sets the stage for future analyses to associate treatments with outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 22 publications
(24 reference statements)
0
17
0
Order By: Relevance
“…51,52 All independent variables were checked for colinearity, and if any pair was highly correlated (r > 0.75), only one of the pair was allowed to enter the models. The discipline-specific articles that follow in this series describe the intensity of specific activities/interventions provided by each treating discipline; [28][29][30][31][32][33][34] this article only addresses time for all therapeutic activities combined.…”
Section: Discussionmentioning
confidence: 99%
“…51,52 All independent variables were checked for colinearity, and if any pair was highly correlated (r > 0.75), only one of the pair was allowed to enter the models. The discipline-specific articles that follow in this series describe the intensity of specific activities/interventions provided by each treating discipline; [28][29][30][31][32][33][34] this article only addresses time for all therapeutic activities combined.…”
Section: Discussionmentioning
confidence: 99%
“…Speech-language pathologists often are consulted to evaluate and treat swallowing, motor speech-voicing, and cognitivecommunication functions. 14,15 It can be particularly challenging to differentiate the type and severity of CCLs and to identify and adapt appropriate cognitivecommunication interventions for individuals with SCI. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…14 In the second stage of SCIRehab, analyses were conducted to better understand the type and amount of interventions that are provided in inpatient rehabilitation. Brougham et al 15 reported a significant difference in time spent in each SLP activity among different neurological groups. There is, however, a paucity of evidence regarding what specific SLP interventions are most important to patients with cognitive-communication needs in order to achieve the best outcomes.…”
Section: Introductionmentioning
confidence: 98%
“…These treatment data were collected by means of the projectspecific electronic data capture system and supplemented by ongoing medical record abstraction and post-discharge patient interviews. The following series of manuscripts offer an overview of the multidisciplinary SCI rehabilitation process 11 and a detailed analysis of treatments provided by physical therapy, 12 occupational therapy, 13 therapeutic recreation, 14 speech language pathology, 15 psychology, 16 nursing, 17 and social work/case management. 18 The data presented cover interventions received by the 600 patients enrolled during the first year of the SCIRehab Project at six collaborating SCI rehabilitation facilities led by Craig Hospital, Englewood, CO and including Carolinas Rehabilitation, Charlotte, NC; The Mount Sinai Medical Center, New York, NY; National Rehabilitation Hospital, Washington, DC; Rehabilitation Institute of Chicago, Chicago, IL; and Shepherd Center, Atlanta, GA. A total of 141 938 treatment sessions are included in the 107 804 hours of therapy and education analyzed in this series of articles.…”
Section: Indiana University Indianapolis In Usamentioning
confidence: 99%